Orature on Literature: the Case of Abba Gärima and His Gospel - Alehegne, Mersha (Aethiopica, 2017)
This paper presents oral narratives told about Abuna Gärima, one of the so called Nine Saints, and his evangelical mission in northern Ethiopia. The narratives presented in the paper discuss different issues: where and how did he write his Gospel, which is believed to be the first Ethiopic Gospel, and the oldest known manuscript in the literary culture of the country; the different miracles the Saint performed during his years of service at the monastery; and how he is commemorated in the people’s popular songs and qǝne, a unique style of Gǝʿǝz poetry. These narratives were collected through oral interviews made with individuals who relate themselves to the monastery which is believed to have been founded by the Saint.